Post-traumatic Pseudoaneurysm of a Branch of Facial Artery - Tong, Khaw Chok; MD Daud, Mohd Khairi; Khairuddin, Nor Khairina; Bakin, Salinawati (Malaysian Journal of Medicine and Health Sciences, 2022)
Pseudoaneurysm which is also known as a false aneurysm is caused by extravasation of blood from the injured vessel wall which is contained by the surrounding soft tissue. It does not contain any layer of the vessel wall and can expand as more and more blood collects. We are reporting a case of an 18-year-old Indian gentleman who presented with complaint of left neck swelling after being involved in a motor vehicle accident. Examination showed a softly pulsating swelling at the angle of the left mandible. CT angiogram revealed a pseudoaneurysm of a branch of the left facial artery. The pseudoaneurysm was embolized by using histoacryl glue. Pseudoaneurysm should be considered as a differential diagnosis in patients with a pulsatile mass after trauma.